Effect of biochar and hydrochar of pistachio residues on physical quality indicators of a sandy loam soil - Daneshvar, Shahrzad; Mosaddeghi, Mohammad Reza; Afyuni, Majid (Geoderma Regional, 2024)
The carbonization of agricultural residues into carbon-rich biochars can be considered as one of the practical methods in sustainable management. The objectives of this study were to: (i) investigate and compare the chemical, physical and micromorphological properties of biochar and hydrochar produced from pistachio (Pistacia vera) residues, and (ii) compare the effects of these chars on the physical quality of a sandy loam soil (classified as Typic Haplocalcids) in pistachio orchards. The physical and chemical characteristics of the biochar and hydrochar were determined. Scanning electron microscopy images showed that hydrochar had a spherical pore structure while the biochar had elliptical pores. The chars were different in terms of functional groups, ratio of elemental composition, and electrical conductivity. Both chars were added at the rates of 0, 1 and 2%w/w to the soil and incubated for nine months under wet and dry cycles. Then, soil physical indicators including bulk density (ρb), dry and wet aggregate stability, water retention curve, saturated water content (θs), field capacity (θFC) and plant available water (PAW) were determined. The results showed that the hydrochar and biochar application had no significant effect on the ρb and dry aggregate stability. However, the percentage of water-stable aggregates larger than 0.25 mm increased at the rate of 1%w/w of chars in comparison with the control. The θs, θFC and PAW increased at both rates of chars when compared with the control. The residual water content (θr) increased at the rate of 1%w/w of chars compared to the untreated soil. It can be concluded that chars of pistachio residues can affect soil physical quality indicators and pore size distribution by the means of different mechanisms like the effect of morphological characteristics of chars, forming complexes between the soil particles, and creating hydrophobic coatings on the soil particles and aggregates. •Biochar and hydrochar of pistachio residues improved soil physical quality indicators.•Hydrochar had a spherical pore structure while the biochar had elliptical pores.•Chars did not significantly affect bulk density and percent of dry-sieved aggregates.•Chars increased water-stable aggregates, field capacity and plant available water.•It seems that the application rate of chars is more important than their types.